Somatic healthcare utilisation patterns among older people with intellectual disability: an 11-year register study - Magnus Sandberg; Gerd Ahlström; Anna Axmon; Jimmie Kristensson (BMC, 2016)
Abstract Background People with intellectual disabilities (ID) are known to have more diseases and are believed to start aging earlier than the general population. The population of older people with ID is growing, but knowledge about their use of healthcare is limited. This study aimed to explore somatic healthcare utilisation patterns among people with ID living in Sweden, in comparison with the general population from 2002 to 2012. Methods Participants were a group of people with ID (n = 7936) aged 55 years and older in 2012, and an equal-sized, birth year and sex matched, general population sample (n = 7936). Participants were divided into age groups of 5-year intervals. Data regarding in- and outpatient care were collected from the Swedish National Patient Register. Results In the younger age groups, the ID group had higher healthcare utilisation compared with the general population sample, with higher risks for planned and unplanned somatic in- and outpatient care, particularly for unplanned inpatient registrations. Decreasing patterns were seen with age; with lower risks in the ID group for the oldest age groups. This was most evident in planned somatic in- and outpatient care. In those with at least one registration, the ID group had a longer unplanned length of stay in the younger age groups, but fewer planned visits to physicians in somatic outpatient care compared with the control group. Conclusions Compared with the general population, people with ID show higher healthcare utilisation in younger age groups. Healthcare utilisation decreases with age, and in old age, fewer people with ID use healthcare compared with the general population. The barriers to accessing planned healthcare for older people with ID need more investigation.